Facilitators and barriers of help-seeking for persons with dementia in Asia—findings from a qualitative study of informal caregivers - Jeyagurunathan, Anitha; Yuan, Qi; Samari, Ellaisha; Zhang, Yunjue; Goveas, Richard; Ng, Li Ling; Subramaniam, Mythily (Frontiers in Public Health, 2024)
The deterioration of persons with dementia makes their caregivers key players in their helpseeking process. This study aimed to identify the facilitators and barriers to help-seeking for persons with dementia (PWD) in Asia from the perspective of their informal caregivers.A qualitative methodology was adopted in the current study. Twenty-nine informal caregivers of PWD in Singapore were interviewed between April 2019 and Dec 2020. All interviews were audio-recorded and transcribed verbatim for the analysis.The transcripts were analyzed using inductive thematic analysis. The results revealed four major themes with 12 sub-themes, including: 1. Barriers to diagnosis seeking (i.e., lack of knowledge and awareness of dementia, emotional denial, resistance from PWD, and delays in the healthcare system); 2. Facilitators of diagnosis seeking (i.e., synergy between awareness of dementia and an active diagnosis seeking intention and incidental diagnosis resulting from seeking treatment for comorbid conditions); 3. Barriers to treatment seeking (i.e., challenges from PWD and disease, challenges faced by caregivers when treatment seeking for PWD, and challenges imposed by the COVID-19 pandemic); 4. Facilitators of treatment seeking (i.e., caregivers' capabilities of handling PWD, cooperation/compliance from PWD, and an integrated care plan for PWD.The findings highlight the importance of raising public awareness, enabling health professionals to tailor psychosocial interventions better, and improving community support through education on dementia.